2017
DOI: 10.1021/acs.langmuir.6b04334
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Structure-Performance Relation for Surfactants Used as Antiagglomerants for Hydrate Management

Abstract: Molecular dynamics simulations were employed to study the structure of molecularly thin films of antiagglomerants adsorbed at the interface between sII methane hydrates and a liquid hydrocarbon. The liquid hydrocarbon was composed of dissolved methane and higher-molecular-weight alkane such as n-hexane, n-octane, and n-dodecane. The antiagglomerants considered were surface-active compounds with three hydrophobic tails and a complex hydrophilic head that contains both amide and tertiary ammonium cation groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(134 citation statements)
references
References 48 publications
17
117
0
Order By: Relevance
“…Although the methane sII hydrate can be thermodynamically stable at large pressures (>100 MPa), a coexistence between sI and sII methane hydrates is generally observed at moderate pressures, as shown by experiments 30 (similar observations hold for CO 2 hydrates 31,32 ) and simulations 33 . We confirmed that in the timescale of our MD simulations the structure of sII methane hydrate remained intact, consistent with our previous study 8 . Moreover, the underlying assumption in our simulations is that the guest molecules in the hydrates do not affect the properties of the aromatics and the AAs films adsorbed on the hydrate.…”
Section: Simulation Methodologysupporting
confidence: 93%
See 2 more Smart Citations
“…Although the methane sII hydrate can be thermodynamically stable at large pressures (>100 MPa), a coexistence between sI and sII methane hydrates is generally observed at moderate pressures, as shown by experiments 30 (similar observations hold for CO 2 hydrates 31,32 ) and simulations 33 . We confirmed that in the timescale of our MD simulations the structure of sII methane hydrate remained intact, consistent with our previous study 8 . Moreover, the underlying assumption in our simulations is that the guest molecules in the hydrates do not affect the properties of the aromatics and the AAs films adsorbed on the hydrate.…”
Section: Simulation Methodologysupporting
confidence: 93%
“…This assumption is supported by the fact that the interactions between guest molecules are mainly short ranged and that on the hydrate surface there exists a 'quasi-liquid' layer of water 29,34,35 . The sII hydrate was chosen in the present study because it represents the hydrate structure formed in the rocking cell experiments used to test the performance of AAs 8 .…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The former approach allows us to define unambiguously the Cartesian position of the free methane molecule with respect to the AA layer. [36]. Freezing the AA molecules does not impact the location of global and local minima, Z/Z box = 0.27 and Z/Z box = 0.36, respectively, and the FE ∆F 0 ≈ 8.5 kJ/mol.…”
Section: Thermodynamic Propertiesmentioning
confidence: 90%
“…[32][33][34] The molecular structure of this AA film is similar to that discussed previously. 9 We expect these ordered interfacial AA films to delay the transport of methane from the hydrocarbon phase to the aqueous film near the growing hydrate, perhaps affecting hydrate growth as suggested by the results shown in Figure 3. Our results confirm that S4 AAs promote faster hydrate growth compared to S1 and S8 AAs at the early stages of growth (less than ~1.5…”
mentioning
confidence: 93%